Phonon features in terahertz photoconductivity spectra due to data analysis artifact: A case study on organometallic halide perovskites - Marcus, Ruldoph Arthur (2017)
We propose a simple scenario where the superimposed phonon modes on the photoconductive spectra are experimental artifacts due to the invalid formula used in data analysis. By use of experimental and simulated data of CH3NH3PbI3 perovskites as a case study, we demonstrate that a correction term must be included in the approximated thin-film formula used in the literature; otherwise, parts of the spectra with high background permittivity near the phonon-mode resonances might interfere with the transient photoconductivity. The implication of this work is not limited to perovskites but other materials with strong vibrational modes within the THz spectral range.